The 206 kbp mitochondrial genome of Phanerochaete carnosa reveals dynamics of introns, accumulation of repeat sequences and plasmid-derived genes - Wang, Xu; Song, Andong; Wang, Fengqin; Chen, Mingyue; Li, Xiao; Li, Qiang; Liu, Na (International journal of biological macromolecules, 2020)
In this study, the mitogenome of Phanerochaete carnosa was sequenced and assembled by the next-generation sequencing. The P. carnosa mitogenome was composed of circular DNA molecules, with a total size of 206,437 bp. Intron sequence, repeat sequence and plasmid-derived genes together promoted the P. carnosa mitogenome to become the second largest mitogenome in Basidiomycota. Gene arrangement analysis revealed large-scale gene rearrangements between Polyporales mitogenomes, and P. carnosa contained a unique gene order. The number and position classes of introns varied between 14 Polyporales species tested, indicated numerous intron loss/gain events occurred in the evolution of Polyporales. Most core PCGs in the 14 Polyporales species we tested were found subjected to purifying selection. However, the Ka/Ks values of rps3 gene were found >1 between some Polyporales species, indicating pressure of positive selection may exist. Phylogenetic analysis based on the combined mitochondrial gene set obtained well-supported tree topologies, and P. carnosa was identified as a sister species to Phlebia radiata. This study served as the first report on the mitogenome in the family Phanerochaetaceae, which will promote the understanding of the phylogeny, population genetics, and evolution of this white-rot fungus and related fungi.